Analisis Labelling Terhadap Laki-Laki Korban Kekerasan Fisik dan Verbal dalam Toxic Relationship - Kethy Ferawati; Chazizah Gusnita (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Both men and women can become victims of violence in toxic relationships, although incidents of violence against men are generally fewer compared to women. However, it is important not to overlook the fact that men can also be victims in toxic relationships. This research aims to analyze the labeling faced by men who are victims of physical and verbal violence in toxic relationships. The research question asked is how this labeling affects the victims' experiences and perceptions. The theory used in this research is labeling theory. This research involved three victims (X, Y, and Z) and one psychologist (AR) as research subjects. The research method used was in-depth interviews to gain a deep understanding of the victims' experiences and psychologists' perspectives regarding labeling in the context of toxic relationships. This research uses a qualitative method with a descriptive analysis approach technique. Research findings show that labeling men victims of physical and verbal violence often has a negative impact on their mental and emotional well-being, with stigmatization and gender stereotypes affecting how they view themselves and communicate their experiences. The implications of this research are the importance of awareness and support for men who are victims of violence in toxic relationships, as well as the need for a gender-sensitive approach in discussing the issue of violence in toxic relationships.